Pertanggung Jawaban Perusahaan Pemilik Kapal terhadap Kasus Pencemaran Lingkungan sebagai Akibat Tumpahaan Minyak Muatan Kapal Laut di Indonesia - Nilawati Yuddin; Wiwik Sri Widiarty; Aartje Tehupeiori (Syntax Idea)
This academic article aims to analyze the liability of shipowners for cases of environmental pollution resulting from oil spills by ships in Indonesia. Indonesia, as an archipelagic nation with significant maritime traffic, faces serious environmental pollution risks due to oil spills from maritime vessels. This research explores the legal aspects related to the liability of shipowners for environmental damage caused by oil spills in Indonesian waters. The article discusses the legal framework governing the responsibility of ship-owning companies, law enforcement procedures, and compensation responsibilities for environmental losses. Additionally, the research analyzes common issues that arise in oil spill cases, including difficulties in measuring environmental impacts, as well as the economic and social losses resulting from pollution. This analysis considers how existing legal regulations in Indonesia govern the liability of ship-owning companies in cases of environmental pollution, as well as the effectiveness of law enforcement in practice. The research also evaluates the challenges in handling oil spill cases and identifies efforts that can be improved to reduce negative impacts on the environment and society. The research findings indicate the need for improvements in the implementation and understanding of legal aspects related to shipowners' liability for oil spills in Indonesia. This article contributes to a deeper understanding of the legal framework governing the responsibility of ship-owning companies in cases of environmental pollution and encourages improvements in regulations and more sustainable industry practices in addressing environmental pollution issues caused by oil spills.